Kajian Teknis Penyelesaian Residu Pendaftaran Tanah Sistematik Lengkap di Kantor Pertanahan Kota Semarang - Raihan, Muhammad; Pujiriyani, Dwi Wulan; Puri, Widhiana Hestining (Sekolah Tinggi Pertanahan Nasional, 2023)
ABSTRACT The Complete Systematic Land Registration Program (PTSL) is one of the initiatives of the Ministry of Agrarian and Spatial Planning/National Land Agency to register land ownership throughout Indonesia. In its execution, the PTSL program still gives rise to various issues, including cluster 3. The emergence of Cluster 3 poses a substantial challenge to the attainment of the PTSL program's objectives. This circumstance is plausible due to cluster 3 (referred to as